Implementasi MB-KM Melalui Metode Mengajar Bahasa Model Pembelajaran Student Center Learning di SMP Gema 45 Surabaya - Rashiva, Ade Rizma; Subargo, Yopi Lutfi; Baharuddin, Fahyuni (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to develop teaching strategies for 8th grade junior high school students, so that the transfer of knowledge oriented towards creativity and student independence or called Student Center Learning (SCL) can be well implied, according to Permendikbud No. 3, 2020 pertains to MB-KM. This type of research is descriptive qualitative using Outcome Based Education (OBE) approach. The focus of this research is 1) Teaching techniques oriented to Student Center Learning (SCL); 2) The advantages and disadvantages of SCL-oriented teaching techniques; 3) Implementation of the discussion method in the learning of eighth grade students of SMP Gema 45 Surabaya. The subjects of this research are seventh semester students, Faculty of Psychology, University of 45 Surabaya, while the object of research is students of SMP Gema 45 Surabaya, eighth grade. The MB-KM program offered by the University of 45 Surabaya is used as a medium in implementing the practice of teaching Indonesian. Data collection was carried out in three stages. First, observation, 1) students mapped the sample population by coordinating with the SMP Gema 45 Surabaya; 2) determination of teaching class; 3) recording the results of observations in the form of written documentation about the activities carried out during interacting with students. second stage; interviews with 3 groups of 8th grade students. The third stage is the documentation and data analysis process, namely collecting, reducing, presenting, and concluding data. The results showed that the subjects were able to apply the SCL learning method using the discussion method.